THE INFLUENCE OF CONTENT MARKETING ON AZLOE'S PRODUCT PURCHASE DECISIONS PROCESS - Shafa Syahida Islamidina; Erna Maulina; Zaenal Muttaqin (Universitas Nusa Cendana, 2025)
This study aims to analyze the effect of content marketing on the @azloeofficial TikTok on Azloe’s product purchasing decisions through TikTok Shop. This research uses a descriptive verification analysis method. The sampling technique was carried out using simple random sampling. This study uses simple linear regression analysis, correlation coefficient, coefficient of determination, and t-test. Data comes from literature studies, observations, interviews, and questionnaires. The population of this study are followers on the @azloeofficial TikTok account who have purchased Azloe’s products at TikTok Shop. The results of this study state that there is a positive and significant effect of content marketing on TikTok @azloeofficial on the Azloe’s product purchase decision process through TikTok Shop. Multiplatform is the dimension with the largest percentage for content marketing, and need recognition is the dimension with the largest percentage for the purchase decision process. Keywords: Content Marketing; Purchase Decisions Process; TikTok